Fuzzy Controller Algorithm for 3D Printer Heaters - El-Fakharany, A. E.; Atia, M. R.; Abu El-Sebah, M. I. (Journal of Advanced Research in Applied Mechanics, 2020)
3D printing using fused filament fabrication technology requires the printer’s heaters to operate within temperature ranges suitable for the used material, hence a closedloop controller for the heaters is needed. PID controllers are the most widely used. To efficiently design this controller, parameter-tuning must be done which is a timeconsuming process. To save time, tuning could be performed by simulation, but this requires the system’s model. Some system models are difficult to deduce, thus other controllers that are independent of the system model and do not require multiple tuning iterations are used. An example of such controllers is the fuzzy like PI controller. This paper presents the design and implementation of a fuzzy like PI controller. The results for testing the controller are presented.